Laurdan as a Molecular Rotor in Biological Environments - Osella, Silvio; Knippenberg, Stefan (ACS applied bio materials, 2019)
Laurdan is one of the most used fluorescent probes for lipid membrane phase recognition. Despite its wide use for optical techniques and its versatility as a solvatochromic probe, little is known regarding its use as molecular rotor, for which clear evidence is found in the current study. Although recent computational and experimental studies suggest the existence of two stable conformations of laurdan in different membrane phases, it is difficult to experimentally probe their prevalence. By means of multiscale computational approaches, we prove now that this information can be obtained through the optical properties of the two conformers, ranging from one-photon absorption over two-photon absorption to the first hyperpolarizability. Fluorescence decay and anisotropy analyses are performed as well and stress the importance of laurdan's conformational versatility. As a molecular rotor and with reference to the distinct properties of its conformers, laurdan can be used to probe biochemical processes that change the lipid orders in cell membranes.
Keywords: lipid bilayer; molecular mechanics; nonlinear optics; fluorescence anisotropy; phase recognition; quantum mechanics; fluorescence decay time